Tinjauan: Implikasi Parasit Cacing pada Komposisi Tubuh Ternak Ruminansia - Frans Umbu Datta; Nancy Foeh; Nemay Ndaong; Annytha Detha (JURNAL KAJIAN VETERINER, 2023)
The effects of gastrointestinal parasties on feed intake and growth is well-established. The emphasis here is on raising awareness that parasites do have effects on body compositon and meat quality atrributes. Body composition refers to the acceptable balance of lean to fat ratio when animals were parasitised or when they were free of parasites. Rejection of carcases due to parasitism is also covered. It was concluded that parasitic infections at subclinical level lead to reduced quantity and impaired quality of meat indirectly by in protein and energy intake as well as through altering and diverting of protein availability for both body maintenance in the forms of establishing resilience to infection as well as repairing of tissues damaged by parasites at sites of predilection. Ineficiency in meat production and alterations to body composition due to nematode parasitism is very much associated with alterations in nutrient absorption and utilisation.